2020
DOI: 10.1002/brb3.1794
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning is a valid method for predicting prehospital delay after acute ischemic stroke

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The degree of stroke-related knowledge is closely related to prehospital delay, which has been confirmed in previous studies (Alegiani et al, 2019;Yang et al, 2020). The better the knowledge, the more familiar the subjects are with the premonitory symptoms of stroke and the faster is their reaction speed (Yang et al, 2020). This study confirmed the above views.…”
Section: Discussionsupporting
confidence: 88%
“…The degree of stroke-related knowledge is closely related to prehospital delay, which has been confirmed in previous studies (Alegiani et al, 2019;Yang et al, 2020). The better the knowledge, the more familiar the subjects are with the premonitory symptoms of stroke and the faster is their reaction speed (Yang et al, 2020). This study confirmed the above views.…”
Section: Discussionsupporting
confidence: 88%
“…Prehospital delay is determined by when the time from the onset of the incidence until the patient's arrival exceeds 3 h (6). Prehospital delay is the main cause of low thrombolysis rate in patients with AIS (7).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can contribute to the prehospital delay of patients with stroke, including demographic (e.g., age, sex, education, income), clinical (e.g., symptom etiology, symptoms, clinical history, and timing of symptom onset), and cognitivebehavioral (e.g., symptom recognition and perceived severity) factors (6,(8)(9)(10). Various risk factors have been suggested, but controversy persists.…”
Section: Introductionmentioning
confidence: 99%
“…An example is Goto et al's (46) work with simple, interpretable decision-trees for EMS triage. This solution often, but not always (26,77,96,102,118), results in poorer discrimination compared to more complex methods like neural networks and deep learning (42,62,75). The challenge, then, is appropriately applying AI or non-AI methods in consideration of the clinical context and acceptable limits for performance and interpretability.…”
Section: Discussionmentioning
confidence: 99%